Evaluation of levamisole as a treatment for amoebic gill disease of Atlantic salmon, Salmo salar L - Findlay, VL; Zilberg, D; Munday, BL (2000)
Levamisole, a known T-cell stimulator and immunomodulator in mammals, has been demonstrated to enhance resistance to amoebic gill disease in Atlantic salmon, Salmo salar L. When used in fresh water baths, dose rates of 1.25, 2.5 and 5 ppm levamisole stimulated resistance to reinfection with Paramoeba sp. that was evident from 2-3 weeks post-treatment. It is proposed that this response is related to enhancement of the non-specific immune system.